Plant Hormone Response to Low-Temperature Stress in Cold-Tolerant and Cold-Sensitive Varieties of Zanthoxylum bungeanum Maxim - Tian, Jieyun; Ma, Yao; Chen, Yabing; Chen, Xue; Wei, Anzhi (Frontiers in Plant Science, 2022)
Plant growth and survival in nature, its growth process will be affected by various factors from the environment, among which temperature has a greater impact. In recent years, extreme weather has frequently appeared, and the growth of crops has been increasingly affected by the environment. As an important flavoring and Chinese herbal medicine crop, Zanthoxylum bungeanum is also facing the harm of low temperature stress. Plant hormones play a vital role in the response of plants to low temperature. In this study, ultra-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to determine the hormone components of cold-tolerant and cold-sensitive varieties of Z. bungeanum. Combined with chemometrics analysis and weighted gene co-expression network (WGCNA) analysis, the hormone component differences and hormone response strategies of Z. bungeanum under low temperature stress were comprehensively studied. The results showed that there were 45 hormones detected in Z. bungeanum. Among them, there were 7 kinds of components with high content and were detected in both two varieties. At the late stage of low temperature stress, the contents of abscisic acid (ABA) and ABA-glucosyl ester (ABA-GE) in FG were significantly increased, and the latter served as the storage of the former to supplement the active ABA. Orthogonal partial least squares discriminant analysis (OPLS-DA) found that indole-3-carboxylic acid (ICA), indole-3-carboxaldehyde (ICAld), meta-Topolin riboside (mTR), cis-Zeatin-O-glucoside riboside (cZROG) and N6-isopentenyladenosine (IPR) in FG were the up-regulated important difference components, and IPR and 2-Methylthio-cis-zeatin riboside (2MeScZR) in FX were the up-regulated important difference components. There were common crossing points and independent response pathways in response to low temperature in two varieties. WGCNA analysis found that the main hormone components were associated with multiple metabolic pathways including carbon, fatty acid, amino acid and sugar metabolism, indicating that hormone regulation plays an important role in the response of Z. bungeanum to low temperature. This study clarified the hormone response mechanism of Z. bungeanum under low temperature stress, and provided reference and basis for further improving cold resistance of Z. bungeanum and cultivating new varieties.